TEM STUDY OF A SPECIAL GRAIN BOUNDARY IN A SYNTHETIC K-FELDSPAR BICRYSTAL: MANEBACH TWIN - Heinemann S.; Wirth R.; Dresen G. (My University, 2003)
A monoclinic KAlSi3O8 feldspar Manebach twin boundary was synthesized by diffusion bonding and examined using high-resolution transmission electron microscopy. The sharp (001) twin boundary is straight and free of strain. The boundary width is smaller than d001. There is no rigid body shift observed at the twin boundary, and the feldspar structure is arranged symmetrically across (001). The twin boundary structure consists of bridged tetrahedral crankshafts, which are characteristic of the feldspar lattice. The grain boundary structure is in good agreement with the geometrical model of Taylor et al. (1934). The grain boundary composition of K1/2H1/2AlSi3O8 differs from their model.
Keywords: GRAIN BOUNDARY STRUCTURE; K-FELDSPAR; TWINS; DIFFUSION BONDING